Gene and Metabolite Integration Analysis through Transcriptome and Metabolome Brings New Insight into Heat Stress Tolerance in Potato (Solanum tuberosum L.) - Bailin Liu; Lingshuang Kong; Yu Zhang; Yuncheng Liao (Plants, 2021)
Potatoes are particularly vulnerable to elevated temperatures, with short heat stress (6 h) inducing stomatal opening and reducing membrane stability and prolonged heat stress (3-day) decreasing the photosynthetic capacity of potato leaves. The integration of transcriptomics and metabolomics methods demonstrated that 448 heat upregulated and 918 heat downregulated genes and 325 and 219 compounds in the positive and negative ionization modes, respectively, were up- or downregulated in leaves in response to short and prolonged heat stress. Differentially expressed genes enriched in photosynthesis, cell wall degradation, heat response, RNA processing, and protein degradation were highly induced during heat exposure, and differentially expressed metabolites involved in amino acid biosynthesis and secondary metabolism were mostly induced during heat exposure, suggesting a possible role of these genes and metabolites in the heat tolerance of the potato. Metabolite and transcript abundances for the upregulation of flavone and flavonol biosynthesis under prolonged heat stress were closely correlated. Heat-induced gene expression in Arabidopsisthaliana shoots and potato leaves overlapped, and heat stress-responsive genes overlapped with drought stress-related genes in potato. The transient expression of four heat-induced genes in Nicotiana benthamiana exhibited increased heat tolerance. This study provides a new transcriptome and metabolic profile of the potato’s response to heat.